Stratospheric Winds and Rain Effect on HAPS Backhaul Link Performance - Abdulrazak, Lway Faisal (Kurdistan Journal of Applied Research, 2017)
today, fourth generation of mobile communication turn out to be in active mode for several countries and one of the most promisingtechnologies used for a backhaul service is High Altitude Platform Stations (HAPS). While HAPS still suffers from environment effects in stratospheric layer like rain and winds.In this research paper, a study of the effect of the positional instability of HAPS (aircraft category) on the link level performance of an International Mobile Telecommunications Advanced (IMT-Advanced) served by HAPS is presented. The analysis is performed in three different climatic conditions of Malaysia, which is a tropical country. Then two types of radio links have been analyzed – firstly, the end user link which connects aerial station and end user and then, backhaul link that establishes communication between HAPS and Ground Transmission Gateway (GTG). A Problem of fluctuations in the signal level and degrading the performance level had been solved by analyze the behavior of winds in stratospheric layer. Finally, the effect of instability was given in received signal level variation and link availability or percentage outage of the link. Obtained results showed that the link availability of the backhaul link meets the ITU-R recommendations. Lately, it can be said that the results of the service obtained can be used to design the communication network with a higher level of user satisfaction.